2018
DOI: 10.1055/s-0038-1675216
|View full text |Cite
|
Sign up to set email alerts
|

Six Years of Experience in Treating Facial Trauma in the Province of Brescia, Italy

Abstract: Facial trauma is an enormous public health problem with overwhelmingly negative physical and psychological impacts. The authors retrospectively analyzed the incidence, etiology, clinical presentations, and characteristics of facial fractures along with sociodemographic, economic, and cultural factors. They analyzed facial fractures treated from June 2010 to December 2016 at the operative unit. Maxillofacial Adult Surgery Unit, Spedali Civili Brescia, Italy, with particular attention to the associations among a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 43 publications
3
8
0
3
Order By: Relevance
“…17,21 The rate of sports-related maxillofacial fractures determined in the present study is slightly higher than the overall European rate but in line with the rate reported in the recent epidemiology literature in Italy. [22][23][24] In the study's hospital division, the relative percentage of sports-related maxillofacial fractures has risen since 1985, from 6.4% to 11.4% to 13.4% (this study). 25,26 The results of this study confirm the clear prevalence of sports-related maxillofacial injuries in young males, a consequence of their aggressive style of play and high activity level, but also reflecting the higher body mass of males compared to females.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…17,21 The rate of sports-related maxillofacial fractures determined in the present study is slightly higher than the overall European rate but in line with the rate reported in the recent epidemiology literature in Italy. [22][23][24] In the study's hospital division, the relative percentage of sports-related maxillofacial fractures has risen since 1985, from 6.4% to 11.4% to 13.4% (this study). 25,26 The results of this study confirm the clear prevalence of sports-related maxillofacial injuries in young males, a consequence of their aggressive style of play and high activity level, but also reflecting the higher body mass of males compared to females.…”
Section: Discussionmentioning
confidence: 78%
“…25,26 The results of this study confirm the clear prevalence of sports-related maxillofacial injuries in young males, a consequence of their aggressive style of play and high activity level, but also reflecting the higher body mass of males compared to females. 6,7,15,16,22,24,27,28 In this study, among the 30 different sport activities that resulted in maxillofacial fractures, team ball/stick and racquet sports, and in particular soccer, were responsible for more than half of the injuries.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…MFF not only cause serious injuries to the victim but also impose a serious burden on the society due to morbidity, mortality, facial disfigurement, loss of function, and financial expenses associated with the injuries [8, 9]. The incidence, aetiology, types, and associated injuries of MFF vary between different countries and even different areas of the same country due to environmental, socioeconomic, cultural, and lifestyle differences among people [1012]. This study analyzed 473 MFF cases treated at the OMFS Unit, Hospital USM, Kelantan, Malaysia.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent multicentric retrospective study from Southern Italy in 2018 showed that the most frequent cause of facial injuries was assault (30.4%), followed by RTA (27.2%), and falls (23.2%) [32]. In contrast to that, the study done by Bocchialini et al from Brescia, Italy, reported RTA as the main cause of MFF (20%), followed by assault (14.4%), and sports (14.1%) [12]. These findings highlighted the variation in the epidemiology of MFF which changes over time even in a similar area of the same country.…”
Section: Discussionmentioning
confidence: 99%